Information content, signalling hypothesis and share repurchase programs in Poland - Wrońska-Bukalska, Elżbieta (Management, 2014)
The article aims to present the meaning of the share repurchase programs and to identify the reasons of share repurchase and information share repurchase convey to investors. The information comprises the following: signalling better financial prospects or signalling intrinsic value. The article analyses selected statistical data on the listed companies that repurchased their shares. Having carried out research for the selected listed companies, I found that companies are not willing to disclose the reasons for share repurchases. However, if they reveal the reason it is not only cash transfer to shareholders.
Keywords: delnice; delniške družbe; informacije; odkup; prodaja